Professional competencies of students of physical and mathematical specialties - Livia Mesarosh; Месарош Лівіа; Mészáros Lívia (SPC PC «Technology Center», 2021)
Abstract. The article outlines the issues of professional competence of senior students of physical and mathematical specialties. A comparative description of their professional competencies is given, common and specific components are identified. It was found that in combination with traditional pedagogical teaching methods (based on the student's reproductive ac tivity), it is important to introduce the latest methods, which provide special attention to the formation of professional competencies of university graduates. It is substantiated that physics is inextricably linked with mathematics. Mathe matics gives physics the means and techniques of general and accurate expression of the relationship between physical quantities, which are discovered as a result of experiment or theoretical research. Therefore, the content and methods of teaching physics depend on the level of mathematical training. It is shown that the teaching of physics and mathemat ics should be based on the mutual use of elements of mathematics in the course of physics and physical concepts in the study of algebra and the principles of analysis, because it accelerates mental development and formation of scientific worldview of students. The importance of interdisciplinary connections as a component of interdisciplinary integration in order to optimize the educational process is revealed. The question of possibilities of creation of physical and math ematical discipline and a set of competences which future experts should possess is considered. It was found out that for future specialists such an approach would allow to carry out the educational process in accordance with the require ments of modern dynamic educational space, acquire new skills, be more competitive, but at the same time due to a large number of discrepancies in the competences of physics and mathematics.
Keywords: professional competence; scientific worldview; interdisciplinary connections; critical thinking; higher education